Sarsaparilla (Smilax spp.) and Sassafras (Sassafras spp.) - James M. Stephens (EDIS, 2003)
This document discusses sarsaparilla and sassafras, two aromatic herbs with historical and cultural significance. It explains that sarsaparilla is derived from the roots of various Smilax species, commonly found in Florida, and clarifies that it is unrelated to sassafras. Sassafras, a member of the laurel family, is noted for its aromatic leaves, bark, and roots, which contain volatile oils. The document highlights their traditional uses, including beverages and essential oils, and provides botanical and ecological context for their growth in Florida. Original publication date May 1994.